Community Perception of Banda Aceh City of Zakat as a Reduction of Income Tax Payments - Fitria; Yani Prihatina Eka Furda (Budapest International Research and Critics University, 2022)
Zakat and taxes as an important subsystem in supporting the economy. In the view of Islam, zakat is part of an important and mandatory element because it is contained in the fourth pillar of Islam. Tax is an obligation imposed on taxpayers, which must be deposited to the State in accordance with applicable provisions and regulations. Taxes as one of the state revenues have not been able to alleviate poverty and provide prosperity for its people, while zakat is an Islamic teaching with a spiritual dimension that emphasizes the importance of economic welfare (social dimension). The existence of a law regarding the payment of zakat which can be deducted from the tax burden has not been properly socialized. The purpose of this study was to determine the perception of the people of Banda Aceh City towards zakat as a deduction from income tax payments. Research with descriptive qualitative research methods tends to use analysis with a Normative Approach and a Sociological Approach. The researcher uses a normative approach because the content of the research is related to the texts of the Qur'an, and a sociological approach because the researcher interacts with the environment according to social units, individuals, groups and institutions. The research was conducted in Banda Aceh City with the determination of informants carried out purposively. The results of the research on the Banda Aceh City Community's Perception of Zakat as a Reduction in Income Tax Payments that there is a perception of the Banda Aceh City community that there are those who understand and know about forgiveness of Law Number 38 of 1999 concerning zakat management, namely zakat payments can reduce tax payments. Article 180 paragraph (1) of Law Number 11 of 2006 concerning the Government of Aceh states that zakat is used as a source of Regional Original Income (Aceh) and districts/cities whose management is carried out by Baitul Mal Aceh in order to improve the welfare of the people of Banda Aceh City.